Casas nobres em Belém do Pará segunda metade do século XVIII e início do século XIX - MORGADO NETO, José Marques (Universidade Federal do Pará, 2017)
This paper investigates the Noble Houses built in Belém in the second half of the eighteenth and early nineteenth century, identified, selected and analyzed based on literature, documentary and iconographic research. The historic city center of the city mentioned is used as a spatial area where the neighborhoods of Cidade Velha and Campina are inserted. They correspond to the primitive nuclei which shaped the urban space of Belém, former headquarters of the Province and State of Grão-Pará during the Administrative Model Colony in Portuguese America. Knowledge about the type of residential building Noble Houses and subsequent identification of specimens in the center of Belém is to reveal their occurrence in the Amazonian soil in a social, economic and political context specific to the Portuguese Ancient Regime. Three buildings were selected as case study: 1) Solar do Barão de Guajará, 2) the Casa Rosada, 3) and the House of Eleven Windows. At first, the genealogy in the Noble Portuguese House was searched, with an understanding of the symbolic values and semantic variations related to their morphology, as well as the knowledge of its architecture. Subsequently, we investigated the residential architecture of the Aristocracy in the Brazilian colonial settings, systematizing the main features from principles found in Portuguese genesis. Finally, the three selected Noble Houses were analyzed, guided by the knowledge of initial studies of its Portuguese and Luso-Brazilian congeners, establishing analogies among them and recognizing local specificities. The result of this research provides a knowledge basis for a specific genre of residential construction, the Noble House, which enables the identification of other specimens in Belém, and in other locations in the state of Pará, in urban or rural areas, making it also possible more informed interventions when these are necessary for its preservation, for we must know what we restore.